‘English is a Subject that You Should Teach Yourself ’: Power and Learner Identity in the Language Introduction Programme in Sweden - Jenny Bergström (Center for Educational Policy Studies Journal)
This article explores students’ perspectives on English language learning in relation to the Language Introduction Programme in Sweden, which is an individual transitional programme for newly arrived immigrants and seeks to quickly transition adolescents into further education or the job market. High proficiency in English is vital in Swedish society, and insufficient knowledge of English can lead to negative long-term consequences for both individuals and society regarding inequality. The methodology used is based on linguistic ethnography, and the data for this article consists of eight semi-structured interviews with students in the programme at one school. Foucauldian perspectives are used to analyse power and the construction of language ideologies relating to the multilingual English-language classroom and learner identity. The results show that the importance of proficiency in English for a success- ful educational transition from the Language Introduction Programme is rarely communicated to students. Furthermore, English is positioned as a subject of low importance within the organisation. The results also show that monolingual norms and language hierarchies limit the stu- dents’ ability to use their first language when learning English.